Efficacy and Safety of Leflunomide for Refractory COVID-19: A Pilot Study - Qiang Wang; Haipeng Guo; Yu Li; Xiangdong Jian; Xinguo Hou; Ning Zhong; Jianchun Fei; Dezhen Su; Zhouyan Bian; Yi Zhang; Yingying Hu; Yan Sun; et al. (Frontiers Media S.A., 2021)
Background: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) may persist in patients with coronavirus disease 2019 (COVID-19) despite receiving standard care.Methods: In this pilot study of hospitalized adult patients (≥18 years of age), with radiologically confirmed pneumonia who were SARS-CoV-2 positive for more than 28 days despite standard care, were assigned to receive standard of care (SOC, grp I) or leflunomide + SOC (grp 2). After 2 weeks, grp 1 and grp 2 patients who continued to be SARS-CoV-2-positive received leflunomide for 14 days while continuing SOC. The primary outcomes were the rate of and time to SARS-CoV-2 clearance and the 14-day and 30-day hospital discharge rate.Results: 12 patients were enrolled in grp 1 and 15 patients were in grp 2. The 14 days SARS-CoV-2 viral clearance rate was 80.0% (12/15) for grp 2 patients receiving leflunomide vs. 16.7% for grp 1 patients (2/12) (p = 0.002). By day 14, the median time to SARS-CoV-2 clearance was 6.0 days (range 1-12, IQR 1-12) for grp 2 patients. In grp 1, two patients converted to viral negative on days 1 and 6 (p = 0.002). The 14-day discharge rate was 73.3% (11/15) for the grp 2 vs. 8.3% (1/12) for grp 1 (p = 0.001). The 30 days discharge rate was 100% (15/15) for the grp 2 vs. 66.7% (8/12) for grp 1. No severe adverse events or deaths were reported.Conclusion: Leflunomide may improve the SARS-CoV-2 clearance rate and discharge rate in patients with refractory COVID-19. The tolerability of the 14-28 days course of treatment with leflunomide is acceptable. These preliminary observations need to be verified by a large sample size and randomized controlled trial.